Multi-Objective Sizing of Battery Energy Storage Systems for Stackable Grid Applications - Arias, Nataly Banol; Lopez, Juan Camilo; Hashemi, Seyedmostafa; Franco, John F. [UNESP]; Rider, Marcos J. (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The deployment of battery energy storage systems (BESS) is rapidly increasing as a prominent option to support future renewable-based energy systems. However, despite its benefits from a technical perspective, there are still challenges related to its economic viability. On the other hand, sizing BESS considering only their economic viability can be impractical because financial objectives could be in conflict with other aspects, such as battery degradation and grid impact. This article proposes a multi-objective approach to determine the optimal size of BESS providing stackable services, such as frequency regulation and peak shaving. The proposed optimization method comprises financial and technical aspects represented by the payback period, battery life span, and grid impact. Given a set of market rules, a cost-benefit function, a regulation signal, consumption profiles and grid data, an enumerative approach is adopted to provide a set of Pareto optimal solutions. The performance of the proposed method is validated using the regulation market structure from PJM interconnection. Furthermore, a real 240-node distribution grid is used to assess the grid impact via OpenDSS. Simulations demonstrate that the proposed approach is a flexible and practical decision-making tool that investors can exploit when designing new BESS.
Keywords: Battery energy storage systems; frequency regulation; Pareto optimality; peak shaving; stackable services